Christian imperialism : converting the world in the early American republic - Conroy-Krutz, Emily (Ithaca : Cornell University Press, 2015)
"In 1812, eight American missionaries, under the direction of the recently formed American Board of Commissioners for Foreign Missions, sailed from the United States to South Asia. The plans that motivated their voyage were no less grand than taking part in the Protestant conversion of the entire world. Over the next several decades, these men and women were joined by hundreds more American missionaries at stations all over the globe ... In describing how American missionaries interacted with a range of foreign locations (including India, Liberia, the Middle East, the Pacific Islands, North America, and Singapore) and imperial contexts, Christian Imperialism provides a new perspective on how Americans thought of their country's role in the world. While in the early republican period many were engaged in territorial expansion in the west, missionary supporters looked east and across the seas toward Africa, Asia, and the Pacific. Conroy-Krutz's history of the mission movement reveals that strong Anglo-American and global connections persisted through the early republic. Considering Britain and its empire to be models for their work, the missionaries of the American Board attempted to convert the globe into the image of Anglo-American civilization."--Publisher's description.
Introduction : Christian imperialism and American foreign missions -- Hierarchies of heathenism -- Missions on the British model -- Mission schools and the meaning of conversion -- Missions as settler colonies -- American politics and the Cherokee mission -- Missionaries and colonies -- A "Christian colony" in Singapore -- Conclusion : missions and American imperialism.
Includes index.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: American Board of Commissioners for Foreign Missions -- History; American Board of Commissioners for Foreign Missions; Missions, American -- History -- 19th century; Political messianism -- United States -- History -- 19th century; Christianity and politics -- United States -- History -- 19th century; RELIGION -- Christian Ministry -- Missions; Christianity and politics; Missions, American; Political messianism; United States; 1800-1899; Electronic books; History